General equilibrium theory an introduction - Starr, Ross M. (Cambridge Cambridge University Press, 2011)
"General Equilibrium Theory: An Introduction presents the mathematical economic theory of price determination and resource allocation from elementary to advanced levels, suitable for advanced undergraduates and graduate students of economics. This Arrow-Debreu model (known for two of its most prominent founders, both Nobel Laureates) is the basis of modern price theory and of a wide range of applications. The text starts with elementary models: Robinson Crusoe, the Edgeworth Box, and a 2-commodity 2-household 2-firm model. It gives a brief introduction to the mathematics used in the field (continuity, convexity, separation theorems, Brouwer fixed-point theorem, point-to-set mappings, and Shapley-Folkman theorem). It then presents the mathematical general equilibrium model in progressively more general settings, including point-valued, set-valued, and non-convex set-valued demand and supply. Existence of general equilibrium, fundamental theorems of welfare economics, core convergence, and futures markets with time and uncertainty are treated fully. The new edition updates discussion throughout and expands the number and variety of exercises. It offers a revised and extended treatment of core convergence, including the case of non-convex preferences, and introduces the investigation of approximate equilibrium with U-shaped curves and non-convex preferences"--Provided by publisher.
Machine generated contents note: Part I. General Equilibrium Theory: Getting Acquainted: 1. Concept and history of general equilibrium theory; 2. An elementary general equilibrium model -- the Robinson Crusoe economy; 3. The Edgeworth box; 4. Integrating production and multiple consumption decisions: a 2 x 2 x 2 model; 5. Existence of general equilibrium in an economy with an excess demand function; Part II. Mathematics: 6. Logic and set theory; 7. RN: real N-dimensional Euclidean space; 8. Convex sets, separation theorems, and non-convex sets in RN; 9. The Brouwer fixed point theorem; Part III. An Economy with Bounded Production Technology, Supply and Demand Functions: 10. Markets, prices, commodities, and mathematical economic theory; 11. Production with bounded firm technology; 12. Households; 13. A market economy; 14. General equilibrium of the market economy with an excess demand function; Part IV. An Economy with Unbounded Production Technology, Supply and Demand Functions: 15. Theory of production: the unbounded technology case; 16. Households: the unbounded technology case; 17. A market economy: the unbounded technology case; 18. General equilibrium of the market economy: the unbounded technology case; Part V. Welfare Economics and the Scope of Markets: 19. Pareto efficiency and competitive equilibrium; 20. Time and uncertainty: futures markets; Part VI. Bargaining and Equilibrium: The Core: 21. The core of a market economy; 22. Convergence of the core of a large economy; Part VII. An Economy with Supply and Demand Correspondences: 23. Mathematics: analysis of point to set mappings; 24. General equilibrium of the market economy with an excess demand correspondence; 25. U-shaped cost curves and concentrated preferences; Part VIII. Standing on the Shoulders of Giants: 26. Next steps; 27. Summary and conclusion.
Acquired through Health Policy Development Program (HPDP) research grant.
Keywords: Equilibrium (Economics); Economics, Mathematical